An Evaluation of the Academic Performance of Students Enrolled in the Double Major Programmes of Architecture and Civil Engineering - Erkan Yazıcı, Yasemin; YAZICI, GÖKHAN (My University, 2012)
Double major programs allow students to simultaneously obtain diplomas in two related academic programs by satisfying their graduation requirements. Students of architecture and civil engineering at the Istanbul Kultur University can apply for the double major program between the third and fifth semesters of their undergraduate education providing their GPAs are at least 3.00 out of 4.00 and they need to maintain their GPAs above 3.00 to continue the double major program. Although all double major programs are demanding and require keen interest of the students, the double major program is particularly challenging due to the differences in educational models used in engineering and architecture. Engineering education largely depends on classroom teaching and laboratory work whereas the architectural education is centered on the design studios. This paper attempts to evaluate the academic performance of civil engineering and architecture students enrolled in the double major program at the Istanbul Kultur University and outline the challenges of a double major program of engineering and architecture.
Keywords: Architectural Education; Civil Engineering Education; Double Major Programs